Metabolite profiling of leaves and branch of Aquilaria sp. - Mohamed Azmin, Nor Fadhillah; Sheerin, Hamnah; Hashim, Yumi Zuhanis Has-Yun; Rosley, Nur Fatihah Nabilah (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Aquilaria or more famously known as agarwood is one of the most valuable wood in the world. When infected, the tree produces dark resinous, fragrant heartwood that is used in perfumes and cosmetics. Agarwood is also known for its medicinal properties such as wound healing, relieving a cold or cough and being a potential anti-cancer agent. However, the full extent of the characterization in agarwood is very limited for such a valuable tree. A multivariate statistical technique known as Multiway Principal Component Analysis (MPCA) is utilized to unmask the underlying patterns in the dataset. The dataset comprises of 24 samples that comes from the leaf and branch of three different Agarwood species; crassna, malaccensis and subintegra, both infected and non-infected. The samples contain mass-to-charge ratio and abundance of each metabolite, obtained from Ultra High Performance Liquid Chromatography - Mass Spectrometry (UHPLC-MS). The result of MPCA obtained concluded that A. malaccensis and A. crassna are most similar to each other. A. Crassna was the most unique, having also both the leaf and branch be very different from each other. Whether the tree was infected or non-infected, it had very little influence in terms of the metabolites. This conclusion seems reasonable as subintegra can only be grown in Thailand while malaccensis and crassna can be grown in most part of Southeast Asia. MPCA is a useful tool to reduce the dimensions of the data and make it easier to visualize.